Early Changes in Clinical Characteristics after Emergency Department Therapy for Acute Heart Failure Syndromes: Identifying Patients who Do Not Respond to Standard Therapy - Collins, Sean P. (2012)
AIMS: Clinical trials for acute heart failure syndromes (AHFS) have traditionally enrolled patients well after emergency department (ED) presentation. We hypothesized a large proportion of patients would undergo changes in clinical profiles during the first 24 hours of hospitalization and these changes would be associated with adverse events. METHODS: We evaluated a prospective cohort of patients with clinical data available at ED presentation and 12–24 hours after ED treatment for AHFS. Patients were categorized into distinct clinical profiles at these time points based on: 1) systolic blood pressure- a. hypertensive [>160 mmHg]; b. normotensive [100–159 mmHg]; or c. hypotensive [<100 mmHg]; 2) moderate to severe renal dysfunction [GFR ≤ 60 ml/min/1.73 m(2)]; and 3) presence of troponin positivity. A composite outcome of 30-day cardiovascular events was determined by phone follow-up. RESULTS: In the 370 patients still hospitalized with data available at the 12–24 hour time point, 196 (53.0%) had changed their clinical profiles, with 117 (59.7%) improving and 79 (40.3%) worsening. The composite 30-day event rate was 16.9%. Patients whose clinical profile started and stayed abnormal had a significantly greater proportion of events than those who started and stayed normal (26.1% vs. 11.3%; p=0.03). CONCLUSION: Patients with abnormal clinical profiles at presentation that remain abnormal throughout the first 12–24 hours of hospitalization are at increased risk of 30-day adverse events. Future clinical trials may need to consider targeting these patients, as they may be the most likely to benefit from experimental therapy.